The Effect Of Bacillus Subtilis On The Bacterial Content In Rabbits Caeci - Eman, F. Farag (Egyptian Society for Animal Management, 2020)
In the present study, the effect of B. subtilis (107cfu/gm) supplemented to the basal diet of two groups of New Zealand rabbit of 28 days (n=15/group) on the count of commensal microflora ( Bifidobacteria and Lactobacilli spp.) and some opportunistic pathogens (E. coli and C. perfringens type A) in the rabbit caeci was investigated. Results indicated that the count of Bifidobacteria and Lactobacilli spp. are significantly increased at all intervals (7, 14, 28 and 40 days post supplementation) in the supplemented group compared with non-supplemented group with P< 0.001. On the other hand, there is a significant decrease in the count of E. coli and C. perfringens specially at 40 days post supplementation from (5.8 log 10 cfu ±0.06) to (3.1 log 10 cfu ±0.07) and from (4.8 log 10 cfu ±0.09) to (2.3 log 10 cfu ±0.09) respectively with P< 0.001. B. subtilis proved to be tolerant to the simulated gastric and intestinal juice for one hour (100% tolerance). However, after two hours, the tolerance to the gastric juice decreased to 70%, with no effect of the artificial intestinal juice on the viability of the organism. In vitro, the antimicrobial effect of B. subtilis on C. perfringens type A by well diffusion method showed an inhibition zone of 10 mm. Results of in vitro effect of B. subtilis on C. perfringens count showed that at 103 dilutions of C. perfringens, its count was reduced 2.1×105 to 3×104 after adding B. subtilis, while at dilution of 102, the count was reduced from 2.4×105 to 7×103cfu/ml after adding B. subtilis. It could be concluded that B. subtilis can be used as a probiotic in rabbits ration due to its ability to increase the commensal microflora count beside its antibacterial effect against some opportunistic pathogens.